Effects of Soaking Duration and Red Onion Extract Concentration on Celery Seed Germination - Siahaan, Limartaida; Yanti, Yus Dwi; Susianti, Helda; Palupi, Dora; Mahmudin; Martin, Riky (Research and Social Study Institute, 2025)
Background: Celery (Apium graveolens) is a horticultural crop with significant economic and culinary value, particularly in Indonesia, where leaf celery is more commonly cultivated. Despite growing interest in hydroponic farming in regions such as Bangka Belitung, celery cultivation remains limited due to challenges in seed germination, especially under lowland and hot climate conditions. Celery seeds are known for slow and inconsistent germination due to hard seed coats and naturally occurring germination inhibitors like coumarin. Seed soaking in plant growth regulators (PGRs), including natural alternatives such as red onion (Allium cepa L) extract—rich in gibberellins and auxins—has been proposed to enhance germination and seedling vigor.Aims & Methods: This study aimed to investigate the effects of different soaking durations (24 and 48 hours) and concentrations (0%, 10%, 20%, and 30%) of red onion extract on the germination performance of celery seeds.Result: The results of this study indicate that a 24-hour soaking duration is the most effective in enhancing celery seed germination as under these conditions, the seeds experience only brief exposure to low oxygen levels. However, soaking seeds in red onion extract at concentrations of 10% to 30% resulted in lower germination parameters compared to the 0% because the concentration is suspected to be too high for celery seeds. Analysis of the interaction between soaking duration and extract concentration revealed that control seeds (without soaking or directly sowing) achieved germination performance comparable to the best treatment combination in terms of germination power, germination speed index, and mean germination time. At the same time, the highest vigor index and seedling length were observed in seeds treated with 10% red onion extract for 24 hours, which also showed similar performance to the control treatment.